2018
DOI: 10.1108/jes-07-2017-0175
|View full text |Cite
|
Sign up to set email alerts
|

Investor confidence and mutual fund performance in emerging markets

Abstract: Purpose The purpose of this paper is to investigate the impact of investor confidence on mutual fund performance in two relatively vulnerable but leading emerging markets, India and Pakistan. Design/methodology/approach A pooled ordinary least squared (OLS) model is used to look at two alternative measures of investor confidence and test for the relationship between investor confidence and mutual fund returns. To check the robustness of the findings, the authors also implement two-stage least squares and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 64 publications
0
14
0
6
Order By: Relevance
“…Wattanatorn et al (2020) notify that some fund managers frequently terminate their worst underperforming funds. Based on research on a sample free of survivorship bias, Nguyen et al (2018) demonstrate that the predictability in equity funds' mean and risk adjusted-returns can be explained by common factors in stock returns and investment expenses. Nguyen et al (2018) also add that stock selection skill cannot affect the consistency of mutual fund performance.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wattanatorn et al (2020) notify that some fund managers frequently terminate their worst underperforming funds. Based on research on a sample free of survivorship bias, Nguyen et al (2018) demonstrate that the predictability in equity funds' mean and risk adjusted-returns can be explained by common factors in stock returns and investment expenses. Nguyen et al (2018) also add that stock selection skill cannot affect the consistency of mutual fund performance.…”
Section: Methodsmentioning
confidence: 99%
“…Based on research on a sample free of survivorship bias, Nguyen et al (2018) demonstrate that the predictability in equity funds' mean and risk adjusted-returns can be explained by common factors in stock returns and investment expenses. Nguyen et al (2018) also add that stock selection skill cannot affect the consistency of mutual fund performance. This also supported by Rao et al (2017) and Wattanatorn et al (2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 We introduce the definition of greenwashing in Chapter 6, under section 6.1. The TR recognises that lack of investor confidence would have a major detrimental impact on the market for sustainable investments 13 (Nguyen et al, 2018;Alewine-Stone, 2013).…”
Section: Establishing a European Regulatory Framework On Sustainabilitymentioning
confidence: 99%
“…The authors also found that volatility, flows, size, number of stocks, and the expense ratio are important factors of modified turnover. Nguyen et al (2018) revealed that mutual funds returns are correlated with investor confidence, fund size, turnover, expense, liquidity, performance persistence and the age of funds. Apap and Collins (1994) scanned the returns of fifteen internationally diversified mutual funds and commented that the funds' performance is mostly likely driven by the benefits of diversification.…”
Section: Literature Reviewmentioning
confidence: 99%